The Patient's Perspective on Shared Decision-Making in Advanced Parkinson's Disease: A Cross-Sectional Survey Study - Nijhuis, Frouke A. P.; van den Heuvel, Lieneke; Bloem, Bastiaan R.; Post, Bart; Meinders, Marjan J. (Frontiers in Neurology, 2019)
Background: Choosing between deep brain stimulation (DBS), Levodopa-Carbidopa intestinal gel (LCIG), or continuous subcutaneous Apomorphine infusion (CSAI) in advanced Parkinson’s disease is a complex decision. It is paramount to combine evidence with the professional’s expertise and the patient’s preferences. The patient’s preferences can be elicited and integrated into the treatment choice through shared decision-making. Objective: In this cross-sectional survey study we explored patient’s involvement in decision-making and identified facilitators and barriers for shared decision-making in advanced Parkinson from the patient’s perspective. Methods: We invited 180 Dutch persons with Parkinson who started DBS, LCIG, or CSAI in the previous three years to complete a questionnaire. Questions covered three topics; 1) preferred and experienced roles in the decision process for an advanced treatment, 2) information needs to make a decision and actually received information, and 3) factors that had positively or negatively influenced shared decision-making. Results: 121 participants completed the questionnaire. The large majority preferred to be involved in the decision-making (93%), and most respondents had experienced an active role (85%). In about half of the respondents (47%) their preferred role did not match their experienced role; 28% had a more active role than they would have preferred. Although 77% perceived to be fully informed at the time of decision, only 41% stated they knew all three therapeutic options. Participants identified the most important facilitators for shared decision-making at the patient’s level (i.e., perceiving the decision to be his own choice), at the neurologist’s level (i.e., having expertise on all treatment options, and taking time for the decision), and within the professional-patient relationship (i.e., trust, and having an open discussion). Main barriers for shared decision-making existed at the patient’s level (i.e., perceiving there is no choice), neurologist’s level (own treatment preference), and organizational level (i.e., no research available that compares treatments, multiple professionals involved, and lack of consultation time). Conclusions: Patients want to be involved and feel involved when choosing an advanced treatment, but often do not know all treatment options. Implementation of true patient involvement needs personalized information provision on all treatment options and improvement on how this information is communicated.